Fused in sarcoma (FUS) protein lacking nuclear localization signal (NLS) and major RNA binding motifs triggers proteinopathy and severe motor phenotype in transgenic mice. - Shelkovnikova, T; Peters, O; Deykin, A; Connor-Robson, N; Robinson, H; Ustyugov, A; Bachurin, S; Ermolkevich, T; Goldman, I; Sadchikova, E; Kovrazhkina, E; Skvortsova, V; et al. (2013)
Dysfunction of two structurally and functionally related proteins, FUS and TAR DNA-binding protein of 43 kDa (TDP-43), implicated in crucial steps of cellular RNA metabolism can cause amyotrophic lateral sclerosis (ALS) and certain other neurodegenerative diseases. The proteins are intrinsically aggregate-prone and form non-amyloid inclusions in the affected nervous tissues, but the role of these proteinaceous aggregates in disease onset and progression is still uncertain. To address this question, we designed a variant of FUS, FUS 1-359, which is predominantly cytoplasmic, highly aggregate-prone, and lacks a region responsible for RNA recognition and binding. Expression of FUS 1-359 in neurons of transgenic mice, at a level lower than that of endogenous FUS, triggers FUSopathy associated with severe damage of motor neurons and their axons, neuroinflammatory reaction, and eventual loss of selective motor neuron populations. These pathological changes cause abrupt development of a severe motor phenotype at the age of 2.5-4.5 months and death of affected animals within several days of onset. The pattern of pathology in transgenic FUS 1-359 mice recapitulates several key features of human ALS with the dynamics of the disease progression compressed in line with shorter mouse lifespan. Our data indicate that neuronal FUS aggregation is sufficient to cause ALS-like phenotype in transgenic mice.